Modifikasi Design Process Bonding untuk Menekan Jumlah Defect Unit pada Mesin Bonding Micro USB di PT. EX Batam Indonesia - Nimatul Mamuriyah; Alfian Aziz Nasution (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
PT EX Batam Indonesia is a company engaged in the production of electronic parts. One type of product that is produced at PT EX Batam Indonesia is a waterproof jack and micro usb. High total production per month requires PT EX Batam to use effective production machines and high efficiency. One of the machines used in the production of waterproof jacks and micro usb is a bonding machine. This machine functions to automatically pour epoxy liquid on the surface of the waterproof jack or micro USB with a predetermined pour point. The room temperature factor greatly affects the performance of the machine and the type of epoxy used. The bonding machine for the B34 series is a bonding machine that has the lowest yield among the existing machines because the rate of reject units it produces is quite high, therefore improvements to this machine need to be made so that the number of rejects can be reduced. By adding a heater that is installed on this machine where the temperature can be set according to the needs of the epoxy liquid used, so that the epoxy can flow evenly. Research results from improvements made to the B34 series bonding machine were able to reduce reject units by 2% of total production, previously rejects reached 3% of total production.